A Unique Case of Replantation of Previously Replanted Fingers - Ravindra Bharathi; Praveen Bhardwaj; Vigneswaran Varadharajan; Hari Venkatramani; S Raja Sabapathy (Indian Journal of Plastic Surgery)
Replantation of digital amputations is now the accepted standard of care. However, rarely will a replantation surgeon be presented with amputated fingers which have been previously replanted. In our literature search, we could find only one publication where a replanted thumb suffered amputation and was successfully replanted again. We report the technical challenges and the outcome of replanting two fingers which suffered amputation 40 months after the initial replantation and were successfully replanted again. Replantation was critical since the amputated fingers were the only two complete fingers in that hand which had initially suffered a four-finger amputation. The second-time replantation of previously replanted fingers is reported to allay the concern of the reconstructive surgeon when faced with this unique situation of “repeat amputation of the replanted finger.” Second-time replantation is feasible and is associated with high-patient satisfaction. Replantation must be attempted especially in the event of multiple digit amputations.